Presuppositions and Implicatures in Comic Strips - Ienneke Indra Dewi (Lingua Cultura, 2008)
Article aimed to find out the role of presuppositions, implicatures, as well as to see the maxims violated or flouted in the comic strips i.e. to whether there is a miscommunication among the characters in the comic strips. Data were taken from the three comics, those are Peanuts, Andy, and Tintin, and were analysed based on the pattern that the sender made a presupposition before transferring information and the receiver would try to get the implied message. The results show that presuppositions and implicatures are much influenced by the background knowledge. The more the speaker and hearer know each other’s background, the better presuppositions and implicatures they make and finally, the less miscommunication occurred.